Systemic humoral immune status in individuals recovered from Epstein–Barr virus (EBV) infection - A.M. Popova; O.V. Volobuieva; I.V. Belozorov (Journal of V. N. Karazin Kharkiv National University: Series Medicine, 2025)
Background. EBV infection is one of the most common in the world. The steady increase in the number of diseases caused by this virus, both among adults and children, necessitates a comprehensive study of its effects on the human body and, above all, on the immune system, and the development of effective methods of prevention and treatment.